Effect of Scraping on Humus Content of Heavy Textured Soil Degraded by Excess Waters - Nagy Pál Máté; Jobbágy Ján; Tuba Géza; Kovács Györgyi; Zsembeli József (Acta Technologica Agriculturae, 2024)
On low-lying soils with a high clay content and poor water conductivity, excess water regularly appears after almost every rainy winter causing soil degradation, which leads to yield failures and/or losses. To outlet the harmful excess surface, waters needs appropriate ameliorative and agrotechnical operations. Among them, scraping represents a suitable intervention into soil structure involving the complete conversion of the micro-topography of the land. The humus content of the soil is a determining factor in terms of soil fertility; therefore, it must be preserved even when drastic tillage operations are carried out on a plot. Our research aimed to assess the effect of scraping on the humus content of the soil on three plots with a heavy textured Vertisol endangered by excess waters. Scraping was used on these plots to create a homogeneous topography and surface with a slight slope to get rid of excess water when it appears. It was established that scraping did not cause humus loss on a plot scale, and it resulted in an evener organic matter distribution, hence a potentially more homogenous yield within the ameliorated plots.